2011
DOI: 10.1007/s12671-011-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Mindfulness Mediates the Relation Between Meditation Experience and Psychological Well-Being

Abstract: A well established notion in Buddhist literature is that meditation practice improves the ability to be mindful in daily life which in turn promotes psychological wellbeing. In order to test this hypothesis the relations between meditation experience, five mindfulness facets and psychological well-being were studied in a sample consisting of Buddhist meditators, Western mindfulness meditators and non-meditators. The meditators scored higher than nonmeditators on all mindfulness facets except Describe, but when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 27 publications
(58 reference statements)
6
38
2
3
Order By: Relevance
“…In long-term meditators and matched nonmeditators, Baer et al (2008) found that a significant association between duration of meditation experience and psychological wellbeing was completely accounted for by increased mindfulness skills. Similar findings were reported by Josefsson, Larsman, Broberg, and Lundh (2011). These studies support the idea that increased mindfulness skills mediate the beneficial effects of mindfulness training and long-term meditation practice.…”
supporting
confidence: 88%
“…In long-term meditators and matched nonmeditators, Baer et al (2008) found that a significant association between duration of meditation experience and psychological wellbeing was completely accounted for by increased mindfulness skills. Similar findings were reported by Josefsson, Larsman, Broberg, and Lundh (2011). These studies support the idea that increased mindfulness skills mediate the beneficial effects of mindfulness training and long-term meditation practice.…”
supporting
confidence: 88%
“…In addition, the data were consistent with a model in which trait mindfulness mediates the relationship between extent of meditation practice and several outcome variables, including fear of emotion, rumination, and behavioral self-regulation. In two other studies, facets of trait mindfulness were found to mediate the relationship between meditation experience and psychological well-being in combined samples of meditators and non-meditators (Baer et al, 2008; Josefsson, Larsman, Broberg, & Lundh, 2011). In addition to correlations with self-report measures, research has examined behavioral and neurobiological correlates of mindfulness meditation.…”
Section: Correlational Research On Mindfulness and Psychological Healthmentioning
confidence: 85%
“…Higher non-reactivity to inner experience was related to lower mood disturbance. Research with experienced meditators and non-meditators suggests the ability to be nonreactive to inner experience is highly related to meditation experience and is most likely to mediate psychological health outcomes [76]. …”
Section: Discussionmentioning
confidence: 99%